2022
DOI: 10.1101/2022.02.07.22270242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling “Bayesian brain” theories of autism spectrum disorder

Abstract: BackgroundBayesian theories of perception have provided a variety of alternative mechanistic explanations for autistic symptoms, including (1) overprecise sensations, (2) imprecise priors, (3) inflexible priors, and (4) altered hierarchical learning. Here, we designed a set of experiments to systematically test predictions from each of the four hypotheses in individuals with autism spectrum disorder (ASD).MethodsTwo versions of a two-alternative forced-choice (2AFC) random dot motion task were developed to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Recent neuro-computational theories have identified a variety of mechanisms that could explain atypical sensory processing [ 1 ] and movement control [ 8 ] in autism, but these theoretical accounts are yet to be adequately tested using the types of naturalistic behavioural tasks that autistic people find challenging (but see [ 74 ] for comparison of Bayesian theories of autism in a purely perceptual task). To probe the generative processes responsible, we applied a generative modelling approach to active inference behaviours from both an object lifting paradigm and an interceptive movement task.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuro-computational theories have identified a variety of mechanisms that could explain atypical sensory processing [ 1 ] and movement control [ 8 ] in autism, but these theoretical accounts are yet to be adequately tested using the types of naturalistic behavioural tasks that autistic people find challenging (but see [ 74 ] for comparison of Bayesian theories of autism in a purely perceptual task). To probe the generative processes responsible, we applied a generative modelling approach to active inference behaviours from both an object lifting paradigm and an interceptive movement task.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although the location of predictive gaze fixations may generally be atypical in 4 But see (Schneebeli et al, 2022) for comparison of Bayesian theories of autism in a purely perceptual task.…”
Section: Discussionmentioning
confidence: 99%
“…To address the phenotypic heterogeneity, computational psychiatry [8][9][10][11][12][13][14][15][16][17] has recently cast ASD with the language of probabilistic inference 18 and suggested that individuals within the spectrum (1) have attenuated expectations 19 (2) inflexibly weight predictions relative to sensory observations 20 and/or (3) over-estimate the volatility of their sensory environment and thus are less surprised by statistically unlikely events 21 . Critically, each of these computational accounts suggest that the learning of context-dependent statistical regularities (i.e., "contextual priors 22 ") is abnormal (e.g., slow 23,24 ) in ASD.…”
Section: Mainmentioning
confidence: 99%